Pengaruh Upah, Insentif Dan Tunjangan Terhadap Kinerja Karyawan Pada PT Bina Kreatif Swakarsa Di Kota Batam - Nuraeni, Brigida Endah; Sumarya, Edi (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2023)
This thesis aim to determine: 1) the effect of salary on employee performance; 2) the effect of incentives on employee performance; 3) the effect of allowance on employee performance; 4) which influence is more dominant between salary, incentives, and allowance to employee performance. This research includes the type of quantitive descriptive research with hypothesis testing. Data analysis technique used are multiple linear regression, t test, f test, and R2test. Population of this research is employee amount to 55 people. In this research does not use certain sampling technique because of limited population, hence sample taken is amounted to 55 people. The method used in this research is quantitive method through survey approach. The result of research using quantitative analysis method gives the conclusion that both partially and simultaneously variable as salary, incentives, allowance have positive and significant effect to employee performance. Based on the result of the regression equation is known that the three independent variable have direct impact with the dependent variable. This means that if the independent variable are improved, then the performance of employees will increase.